Dietary Vitamin K Restriction and Effectiveness of Vitamin K Antagonists Prescribed at the CNHU-HKM University Cardiology Clinic/BENIN - METONNOU ADANHOUME, CLÉMENCE GERMAINE; Sossa, Charles; SALAMI, Liamidhi (My University, 2023)
Atherosclerotic cardiovascular disease remains one of the leading causes of death worldwide, despite the availability of risk-modifying treatments and lifestyle advice [1]. Antivitamins K (AVKs) belong to the family of oral anticoagulants, widely prescribed in the management of a number of cardiovascular diseases. Patients prescribed these VKAs risk being under-dosed, Wirth inadequate protection against thromboembolism, or over-dosed, with a high risk of hemorr- hage [2]. Studies by Rombouts et al. have shown an interaction between vitamin K intake and oral anticoagulation therapy [3]. Patients treated with VKAs are often advised to restrict their vitamin K intake, but recent data in the literature tend to show the benefits of a balanced diet, with unrestricted consumption of foods containing vitamin K [4]. AnticoagDietary vitamin K intake restriction event thromboembolic events in a number of situations: mechanical heart valve replacement (MHRV), atrial fibrillation (AF), deep thrombophlebitis, and/or pulmonary embolism [5]. The frequency and seriousness of bleeding on anticoagulants make them a dreaded event, and their management must be well codified. Vitamin K, by allowing endogenous hepatic production of factors five to six hours after administration, takes over from the exogenous factors supplied and ensures that correct hemostasis is maintained from the sixth hour until the disappearance of circulating VKA molecules. Rapid antagonization of VKA treatment requires the administration of clotting factor concentrates (commonly known as prothrombin, proconvertin, Stuart factor, anti-hemophilic factor B [AHFB]) and vitamin K. PPSB is the antidote to VKAs. This combination is recommended by Anglo-Saxon learned societies and by Afssaps [6] [7] [8] [9]. The administration of vitamin K is essential in view of the pharmacological properties of coagulation factors. The short half-life (five to six hours) of factor VII limits the duration of action of PPSB [10] [11]. Dietary vitamin K intake restriction was still recommended for patients treated with VKAs at the University Cardiology Clinic of the CNHU HKM in Cotonou. This study examines the influence of dietary vitamin K restriction on the efficacy of VKA treatment at the University Cardiology Clinic of the CNHU HKM in Cotonou (BENIN).
Keywords: Antivitamin K; Dietary Restriction; Vitamin K; Therapeutic Efficacy